2021
DOI: 10.1101/2021.04.01.438129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual variability in the human connectome maintains selective cross-modal consistency and shares microstructural signatures

Abstract: Individuals are different in their behavioural responses and cognitive abilities. Neural underpinnings of individual differences are largely unknown. Here, by using multimodal imaging data including diffusion MRI, functional MRI and MEG, we show the consistency of interindividual variation of connectivity across modalities. We demonstrated that regional differences in individual variability of structural and functional connectomes is characterized by higher variability in association cortices and lower variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…First, a relatively large sample size with repeated structural and functional brain scans is needed. Previously, Camberland et al (Chamberland et al, 2017) and Karahan et al (Karahan et al, 2021) both reported no significant correlation between SC and FC variability at a global level, which could be attributable to the small sample sizes of their studies (Chamberland et al, 2017;Karahan et al, 2021) or the confounds of intrasubject variations (Karahan et al, 2021). In this study, we found that the correlation between FC variability maps before and after regressing intraindividual variance was only 0.41 (0.94 for principal SC variability), highlighting the necessity of removing intraindividual FC variance when studying the relationship between FC and SC variability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…First, a relatively large sample size with repeated structural and functional brain scans is needed. Previously, Camberland et al (Chamberland et al, 2017) and Karahan et al (Karahan et al, 2021) both reported no significant correlation between SC and FC variability at a global level, which could be attributable to the small sample sizes of their studies (Chamberland et al, 2017;Karahan et al, 2021) or the confounds of intrasubject variations (Karahan et al, 2021). In this study, we found that the correlation between FC variability maps before and after regressing intraindividual variance was only 0.41 (0.94 for principal SC variability), highlighting the necessity of removing intraindividual FC variance when studying the relationship between FC and SC variability.…”
Section: Discussionmentioning
confidence: 96%
“…To date, only three studies have examined the relationship between interindividual FC and SC variability patterns. Of them, two studies reported nonsignificant spatial correlations between FC variability and tractography-based SC variability (Chamberland et al, 2017; Karahan et al, 2021), which could be attributable to a relatively small sample size (n = 9 (Chamberland et al, 2017) and n = 29 (Karahan et al, 2021)) and confounds of intraindividual variation (Karahan et al, 2021). A very recent study reported a significant correlation between interindividual variability patterns of FC and tractography-based SC (Mansour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Less myelination might enable greater plasticity in association areas both during development and adulthood [ 114 116 ]. Neural circuits with less myelinated regions have previously been shown to exhibit increased functional and structural variability [ 117 ]. Taken together, these factors might be related to, at least partly, the high susceptibility of our predictive models to population diversity in the default mode network, and other associative cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Less myelination might enable greater plasticity in association areas both during development and adulthood (Glasser & Van Essen, 2011; Timmler & Simons, 2019; Turner, 2019). Neural circuits with less myelinated regions have previously been shown to exhibit increased functional and structural variability (Karahan et al, 2021). Taken together, these factors might be related to, at least partly, the high susceptibility of our predictive models to population diversity in the default mode network, and other associative cortical regions.…”
Section: Discussionmentioning
confidence: 99%